2013
DOI: 10.3109/00207454.2013.801471
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric tonic neck reflex and symptoms of attention deficit and hyperactivity disorder in children

Abstract: One of the particularly important postnatal developmental reflexes that diminish in later stages of development is asymmetric tonic neck reflex (ATNR), which belongs among the so-called primitive reflexes. According to current evidence, certain later developed functions during ontogenesis of the central nervous system tend to replace the primitive reflexes, and their persistence is related to certain specific neuropsychiatric or neurological disorders. According to current knowledge, there is no evidence to wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 23 publications
1
17
0
2
Order By: Relevance
“…According to current findings and the best of our knowledge, there are few reported findings of persisting reflexes in dyslexia11,12 and preliminary findings suggesting that ADHD symptoms could be related to persistence of the primitive reflexes in later developmental stages than is usual 12,13. These studies suggest that further detailed research examining developmental conditions in ADHD is warranted and that such research might have significant consequences for understanding ADHD, dyslexia, and other neurodevelopmental disorders 1113.…”
Section: Introductionmentioning
confidence: 48%
See 2 more Smart Citations
“…According to current findings and the best of our knowledge, there are few reported findings of persisting reflexes in dyslexia11,12 and preliminary findings suggesting that ADHD symptoms could be related to persistence of the primitive reflexes in later developmental stages than is usual 12,13. These studies suggest that further detailed research examining developmental conditions in ADHD is warranted and that such research might have significant consequences for understanding ADHD, dyslexia, and other neurodevelopmental disorders 1113.…”
Section: Introductionmentioning
confidence: 48%
“…Disinhibitory processes related to disturbed motor functions are probably also linked to persisting primitive reflexes that were not sufficiently suppressed in later stages of development. According to some evidence, persisting primitive reflexes may occur in various neuropsychiatric syndromes such as schizophrenia or various forms of dementia5,6,20,23 and have also been observed in patients with dyslexia11,24 and in school-aged children with ADHD12,13,25,26 In our previous study on medicated ADHD children,13 we found that boys had higher levels of ADHD symptoms and that there was little statistically significant difference in persisting primitive ATNR between girls and boys. Moreover, studies that have focused on persistent ATNR in dyslexia11,24 have not reported differences between girls and boys.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serious problem in special education that play very important role in school environment of these children represent various forms of behavioral disorders that in typical forms mainly manifest as uncontrolled and involuntary speech and movements. In many cases these deficits are developmentally influenced and may be specifically linked to increased fatigue and decreased attention that may lead to manifestation of cognitive tiredness or exhaustion and various forms primary reflex behavior related to involuntary movements (Konicarova & Bob, 2013;McPhillips et al, 2000). In addition these children with ADHD and dyslexia are highly sensitive to various psychosocial stressors that make school environment highly specific with respect to relaxed atmosphere in the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…A signal informing about a persistent primary reflex is an unsuitable and undesirable reaction of the nervous system, which affects further development, learning and behaviour. The basic symptoms of persistent primary reflexes include the following: beginning of verbal communication after 18 months of age, thumb sucking until 5 years of age or later, enuresis after 5 years of age, dyspraxia, coordination difficulties, impairment of visuomotor coordination, articulation difficulties, auditory and visual hypersensitivity and many others (Gogate & Hollich, 2016;González, Ciuffreda, Hernández, & Escalante, 2008;Konicarova & Bob, 2012;2013a;2013b;Melillo, 2016).…”
Section: Introductionmentioning
confidence: 99%